Effect of Giardia lamblia Infection on the Cognitive Function of School children - F Partovi; G Khalili; A Kariminia; H Mahmoudzadeh- Niknam (Tehran University of Medical Sciences, 2007)
Background: The association between helminthic parasitic infection and cognitive function has long been recognized, however there are few reports about Giardia lamblia infection. This paper describes a study about the effect of G. lamblia infection on the cognitive function. Methods: One hundred thirty two children infected with G. lamblia from Robat Karim south of western Tehran, Iran were compared with 150 children without any parasitic infection. These two groups were identical in socioeconomic and nutritional status. Cognitive function was assessed using, three tests from Wechsler Intelligence Scale for children and one subset of the Clinical Evolution of Language Function. Results: Comparison of two groups revealed that uninfected children improved significantly more than children who had G. lamblia infection in the tests of Fluency (P< 0.02) and Digit-span Forwards/ Backwards (P< 0.004). Conclusion: Regular stool examination is suggested in areas with low hygienic conditions, since G. lamblia infection might be present without any clinical manifestation.